KOEFISIEN PENYERAPAN BUNYI BAHAN AKUSTIK DARI PELEPAH PISANG DENGAN VARIASI UKURAN SERAT - Novita Suherman; Ihsan Ihsan; Rahmaniah Rahmaniah (JFT : Jurnal Fisika dan Terapannya, 2020)
This study aimed to determine the effect of fiber size of the sound absorption coefficient of acoustic material of banana. In this study, the size of the fiber used is 10 mesh, 20 mesh, and 40 mesh wi th a board thickness of 1cm. The value of the frequency used is 125 Hz, 250 Hz, 500 Hz, 1000 Hz, and 2000 Hz. The result showed that the smaller the size of the fiber, the more high sound absorption coefficient is generated. Good sound absorption coefficient is the mesh size of 40 with a frequency of 125 Hz at a thickness of 1 cm is equal to 0.255. This suggests that the acoustic boards made of banana can be used as a silencer because it meets the ISO 11654 standard.